UPLC–QQQ–MS/MS-based widely targeted metabolomic analysis reveals the effect of solid-state fermentation with Eurotium cristatum on the dynamic changes in the metabolite profile of dark tea. (1st June 2022) - Xiao, Yu; He, Cheng; Chen, Yulian; Ho, Chi-Tang; Wu, Xing; Huang, Yuxin; Gao, Yao; Hou, Aixiang; Li, Zongjun; Wang, Yuanliang; Liu, Zhonghua
Highlights: E. cristatum used in pure-culture fermentation of primary dark tea. Metabolites evolutions of dark tea during SSF were determined by UPLC–QQQ–MS/MS. 574 differential metabolites were detected during SSF of dark tea by E. cristatum . Phenolic acids and flavonoids are the two largest classes of differential metabolites. E. cristatum  is favorable to the accumulation of theabrownins during SSF of dark tea. Abstract: Eurotium cristatum is the predominant fungus and key contributor to the characteristics of post-fermented Fu brick tea (FBT) during manufacturing. In this study, the influence of solid-state fermentation (SSF) with E. cristatum on the chemical profile dynamic changes of dark tea was investigated. Results indicated that total phenolics, flavonoids, theaflavins, thearubigins, and galloyl catechins consistently decreased, degalloyl catechins and gallic acid increased in the initial stage of fermentation and decreased after long-term fermentation, and theabrownins continually increased. UPLC–QQQ–MS/MS-based widely targeted metabolomic analysis revealed that the metabolites of dark tea processed by SSF with E. cristatum were drastically different from the raw material. A total of 574 differential metabolites covering 11 subclasses were detected in the whole SSF of dark tea, and the most drastic changes occurred in the middle stage. Phenolic acids and flavonoids were the two major classes of differential metabolites. A series of reactions such as degradation, glycosylation, deglycosylation, methylation, and oxidative polymerization occurred during SSF. Overall, SSF with E. cristatum greatly influenced the metabolites of dark tea, which provided valuable insights that E. cristatum is critical in forming the chemical constituents of FBT.